Carbon dioxide utilisation by integrated microalgae cultivation process in membrance photobioreactor - Emma Suali (2014)
The CO₂ emission has encouraged the research on C0₂ mitigation by microalgae. However, low carbonation and high dissolved oxygen (DO) of microalgal media in bioreactor were identified as major drawbacks of this technique, besides low C0₂ uptake by microalgae. Thus, this study aimed to increase the carbonation by integrating bioreactor with two types of membrane so that C0₂ uptake by microalgae can be increased during the C0₂ mitigation process. This study used indirect membrane-based bubbling as an alternative to increase carbonation of microalgae, while the selected microalga was evaluated in term of its suitability for C0₂ mitigation. It was found that the selected microalgae, which is a local isolate Chlorella sp. is suitable for C0₂ mitigation and as biomass producer. This microalga is also capable of performing a carbon concentrating mechanism (CCM), which can be manipulated to increase the C0₂ utilisation. The carbonation by using membrane on the other hand was successfully evaluated in term of fouling, bubbling, and dissolved C0₂ (DC0₂). The effect of membrane to remove the dissolved 0₂ (DO) was evaluated in term of DO efficiency and C0₂ uptake by microalgae. It was found that the membrane integration resulted in DC0₂ up to 82%. This is 4 times higher than typical direct bubbling, which only reached 29%. The result of carbonation efficiency was supported by the correlation of C0₂ inlet and accumulated C0₂ concentration with DC0₂. Based on the developed correlation, overall mass transfer coefficient of C0₂ in the membrane was 4.35 x 10⁻² cm2s⁻¹ , making the selected membrane and technique suitable for C0₂ mitigation by microalgae. However, large bubbles were identified as the main reason for low DC0₂ . This causes low C0₂ uptake by microalgae. Thus, the decrease in bubble size decreased C0₂ escape into the bioreactor headspace. The most suitable bubble size for C0₂ mitigation is in the range of 1 mm to 5 mm. The use of membrane for deoxygenation resulted in up to 43% of DO removal. However, the membrane integration removed the DC0₂ up to 11 % compared to non-integrated. The membrane also resulted in microalgae accumulation of 3% of the total microalgae concentration when pumped through the membrane. It may be concluded that overall C0₂ uptake by microalgae can be increased up to 10% through the aid of a membrane. The experimental results show that membrane integration aiding the C0₂ utilisation by microalgae is possible by controlling both operating conditions and C0₂ supply concentration.